Title III of the Helms-Burton Act is consistent with international law. - CLAGETT, Brice M. (1996)
Argues that Title III of the Helms-Burton Act furthers both the development and the implementation of internationa law in an area where enforcement mechanisms allows certain states to violate the human rights of their own citizens and of foreigners.